FIELD AND STORAGE PERFORMANCE OF INDUSTRIAL POTATOES TREATED WITH COBALT AND SILICON - Maha. A. Hussein; Nabeel. J. K. Al-a’amry; Rasha R. Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Two field and storage experiments were conducted at a Research Station affiliated with the College of Agricultural Engineering Sciences / University of Baghdad during the 2023 and 2024 season. To investigate the effect of cobalt chloride at three concentrations 0, 5, and 15 mg. L-1 (C0, C1, C2) and silica gold at four concentrations 0, 5, 10, and 15 ml.L-1 (Si0, Si1, Si2, Si3) to increase tubers production and quality and raise the storage capacity of industrial potato hybrid Hermes as factorial experiment within R.C.B.D. with three replicates. The storage experiment was conducted in the refrigerated warehouse belongs to private sector, following the same design of field experiment, the results revealed that the C1 treatment recorded the highest percentage of ascorbic acid and total phenols in tubers for both seasons while C2 treatment recorded the highest plant productivity and tuber weight in both season and lowest percentage of microbial contamination. The Si2 treatment resulted in the highest activity of catalase enzyme and the lowest weight loss percentage.